Interaction on the Tabletop: Bringing the Physical to the Digital - Hilliges, Otmar; Butz, Andreas; Izadi, Shahram; Wilson, Andy (Tabletops - Horizontal Interactive Displays, 2010)
Current tabletop applications, which go beyond mouse-like input, mostly use gestures and/or tangible objects. Gestures are mostly recognized by matching input to a given set of predefined (scripted) gestures, and tangible input is implemented by recognizing shapes or markers. While this allows exactly the interactions foreseen by the programmer, it can be observed in the real world, that physical artefacts are used much more flexibly and often in unforeseen ways. We describe two of our explorations into tabletop interaction styles, discuss their respective strengths and shortcomings, and then derive a new model for tabletop interaction based on a physics simulation and rich multi touch input. Interaction with this model achieves a very high fidelity to the physical world and allows appropriation of the interface, i.e., the development of individual and unforeseen interactions with the system. We have evaluated our model in different variations and believe that it holds a strong promise for future, highly flexible tabletop interfaces.